Diaphragm valve-controlled air thrust bearing. (May 2017) - Ghodsiyeh, Danial; Colombo, Federico; Raparelli, Terenziano; Trivella, Andrea; Viktorov, Vladimir
Abstract: A low-cost pure pneumatic control is presented as a semi-active compensation to increase the stiffness of pneumatic air bearings. A prototype of the pneumatic control valve was developed for this purpose, and a rectangular air pad was selected for the experiments. Tests for the static performance of the controlled pad showed a significant increase in the stiffness of the bearings. A lumped mathematical model of the system was developed for a quick and accurate design of the pneumatic control. The comparison between the theoretical and experimental results is shown, and the effect of the main parameters on the static performance of the system is discussed. Highlights: New pure pneumatic control valve system is developed. New valve is small and cheap and it can be adapted to any commercial air pads. The static tests shown the significant improvement in the stiffness of air pad. Developed lumped model can adequately describe the performance of the system.